Grand Fundamental Norm as the Ideal Regional Formation Norm: A Study on Indonesian Community Participation - Abdul Kadir; Ahmad Wahidi; Musataklima , Musataklima; Khoirul Anam; Rajaa Hussein Abdulameer (JUSTISI, 2024)
The legal problem in this study is to present local wisdom that is relevant to Pancasila as the grand fundamental norm in the formation of laws and regulations by focusing the analytical study on meaningful participation. This study aims to analyze the grand fundamental norm as an ideal norm and meaningful participation in forming Regional Regulations based on the type of normative juridical research using a statutory and conceptual approach. The data used is secondary data with primary and secondary legal materials, which are processed by checking the completeness, clarity of meaning, suitability, and relevance to the substance of this study, then analyzed using qualitative juridical analysis methods, which are based on the work of juridical reasoning. The novelty of this study emphasizes local wisdom as the primary source and representation of the ideal Pancasila norm (grand fundamental norm) in forming regional regulations through the meaningful participation method. The first study's results show that the grand fundamental norm in forming regional regulations is necessary based on the Indonesian nation's philosophical and sociological values ​​. Thus, Pancasila is the ideal basic norm for implementing Pancasila values ​​, which can be institutionalized realistically in Regional Regulations in Indonesia. Second, the noble culture of the Indonesian nation is the benchmark for Regional Regulations with all the material content and principles in the formation of statutory regulations, namely the principles of justice and transparency with implementation efforts using interactive methods and models of community participation that focus on the form of deliberation to reach consensus. The hope is that this will give birth to participatory Regional Regulations.